The impact of human capital on economic growth: the case of selected Arab countries - Atif Awad,; Noreha Halid,; Ishak Yussof, (Institut Kajian Rantau Asia Barat, 2013)
The overall objective of this article is to investigate the impact of human capital on the economic growth of selected Arab countries, including Sudan, during the period of 1990 to 2010. The study makes use of panel data, and estimates an aggregate production function using a fixed effects model. The basic macroeconomic variables of concern derived from the literature review include the real gross domestic product, capital stock, the labor force, and gross enrolment in primary, secondary and tertiary education levels. The results reveal that human capital development – secondary and tertiary education levels – has a significant impact on the economic growth of Arab countries.